Corrosion of Titanium Alloys Anodized Using Electrochemical Techniques - Jáquez Muñoz, Jesús Manuel; Gaona Tiburcio, Citlalli; Méndez Ramírez, Ce Tochtli; Baltazar Zamora, Miguel Ángel; Estupiñan López, Francisco Humberto; Bautista Margulis, Raúl German; Cuevas Rodríguez, Josefina; Flores de los Ríos, Juan Pablo; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2023)
The anodization of titanium has been an excellent option for protecting titanium and its alloys from corrosive environments such as acids and chloride systems, by generating a homogenous oxide layer. The objective of the current investigation was to evaluate the electrochemical corrosion behavior of alloys Ti-6Al-2Sn-4Zr-2Mo and Ti-6Al-4V anodized in 1MH2SO4 andH3PO4 solutions at a current density of 2.5   10–3 A/cm2. The anodization’s electrochemical characterization was achieved in NaCl and H2SO4 at 3.5% wt. electrolytes. Scanning electron microscopy (SEM) was employed to determine the anodized thickness and morphology. Cyclic potentiodynamic polarization (CPP) and electrochemical impedance spectroscopy (EIS), based on ASTM G61-86 and G106-15 Standards, were the electrochemical techniques mainly employed. The anodized samples presented a change in Ecorr values and a higher passivation zone. The EIS plot showed a higher resistance for samples anodized in H3PO4 and Ti-6Al-2Sn-4Zr-2Mo.